The First Campaign Victory of the Great War: South Africa, Manoeuvre Warfare, the Afrikaner Rebellion and the German South West African Campaign, 1914-1915 - Antonio Garcia - Scherman, Jean-Pierrre (Scientia Militaria - South African Journal of Military Studies, 2020)
Book Review